Association of Anterior and Posterior Occlusal Planes with Skeletal Class I, Class II and Class III Malocclusion - Shrestha, Rosha; Maskey, Suvit; Acharya, Gaurav (Nepal Journal of Health Sciences, 2025)
Introduction: The occlusal plane is a very vital in stomatognathic system and the association between anterior occlusal planes and posterior occlusal plane plays an important role during orthodontic treatments.Objectives: To assess occlusal planes in skeletal Class I, II, III malocclusion and to find the Association of Anterior and Posteriorocclusal planes with skeletal Class I, Class II and Class III malocclusion.Methods: A cross-sectional study was conducted at KIST Medical College using convenience sampling. Lateral cephalograms of 270 adults with Class I, II, III malocclusion were analyzed to assess angular measurements and their relation to skeletal and vertical patterns. Data were analyzed using SPSS version 16, and descriptive statistics (frequencies, percentages, means, and standard deviations) were computed.Results: The skeletal patterns showed significant difference in anterior occlusal plane angle relative to Sella-Nasion plane and Frankfort Horizontal plane among all classes of malocclusion (p-value =0.001**) having a steeper inclined plane in Class II and flat inclined plane in Class III. Posterior occlusal plane in relation to Frankfort Horizontal plane and Sella-Nasion plane showed lowest angle in skeletal Class III and highest in Skeletal Class I patients.Conclusion: The occlusal planes were found to have impact on the jaw base where variation in its angulation of different occlusal planes had affected sagittal and vertical facial patterns. Anterior occlusal plane relative to Sella-Nasion and Frankfort Horizontal were steeper in Class II and flat in Class III, while the Posterior occlusal plane relative to Frankfort Horizontal showed the same value in Classes II and III.